Penyusunan Silabus dan Buku Ajar untuk English for Young Learners di Jage Kastare Foundation - Junaidi, Ahmad; Gunalan, Sasih; Hidayat, Yudha (DARMADIKSANI, 2021)
ABSTRAK Salah satu permasalahan dalam gerakan pengajaran Bahasa Inggris di daerah dengan akses pendidikan rendah adalah kurangnya materi ajar yang dikemas dalam silabus yang fleksibel dan reflektif. Oleh karena itu, kami mengorganisir kegiatan lokakarya penyusunan silabus dan buku ajar untuk program English for Young Learners bersama relawan Yayasan Jage Kastare. Dua belas relawan terlibat dalam penyusunan pelevelan, silabus, dan buku ajar. Hasilnya, program EYL JKF dibagi menjadi empat kelas yaitu Crawler, Walker, Runner, dan Flyer, dengan mengkombinasikan pendekatan Cambridge dengan interpretasi pendidikan Bahasa Inggris kritis. Silabus disusun dengan mengedepankan fleksibilitas pendekatan dan penciptaan kegiatan yang menyenangkan agar siswa mendapatkan kesan yang positif dalam konteks English for Young Learners. Buku ajar tersusun, namun masih terus membutuhkan perbaikan dalam beberapa aspek terutama mengenai hak cipta dan penambahan konten lokal. ABSTRACT One of the issues in the English language teaching movement in areas with low access to quality education is the lack of teaching materials packaged in a flexible and reflective syllabus. Therefore, we organized workshops for the preparation of syllabus and textbooks for the English for Young Learners program with volunteers from the Jage Kastare Foundation. Twelve volunteers were involved in preparing the leveling, syllabus and textbooks. The English for Young Learners program is divided into four classes, namely Crawler, Walker, Runner, and Flyer, by combining the Cambridge approach and critical English pedagogy in content. The syllabus was prepared by prioritizing the flexibility of approach and the creation of fun activities so that students gain a positive impression in their process learning English as young learners. The textbooks were successfully composed, but still needing improvement in many aspects, especially regarding copyright and the addition of more local content.